A familial cluster of coronavirus disease 2019 (COVID-19) caused by one family member during his asymptomatic incubation period. (10th July 2020) - Sang, Hao; Cui, Yan; Lai, Xiaobin; Zhang, Yuyan; Kong, Lingna; Jiang, Xiaoli; Liu, Hui; Zhang, Jie; Ye, Jun; Gu, Wenchao; Fang, Chenfei; Zhang, Huansheng
Abstract: An ongoing outbreak of coronavirus disease 2019 (COVID-19) has rapidly spread in the world, whereas asymptomatic carriers may also play a critical role in the pandemic. We report a familial cluster of COVID-19 caused by one family member before his onset of illness, indicating that it seems to be potentially infectious during the incubation period, even earlier than we expected. Close contact, especially in a small enclosed space, might be the cause of familial transmission. The unsynchronized changes in the clinical symptoms and COVID-19 nucleic acid were found in this case, so consecutive nucleic acid detection of pretty suspected cases was recommended. Family members, especially of whom the confirmed cases contacted with since one incubation period before onset rather than 2 days before onset, should be regarded as close contact and centrally isolated in case of asymptomatic infection already existed in the family.